Enhanced mechanical and electrochemical durability of multistage PTFE treated gas diffusion layers for proton exchange membrane fuel cells - John Felix Kumar, R.; Radhakrishnan, Vijay; Haridoss, Prathap (International journal of hydrogen energy, 2012)
Gas Diffusion Layers (GDLs) of Proton Exchange Membrane Fuel Cells (PEMFCs) are usually subject to polytetrafluoroethylene (PTFE) treatment in a single stage. The impact of multistage PTFE treatment on the mechanical and electrochemical durability of GDLs used in PEMFCs, is reported here. With the same total amount of PTFE in the GDL, substrates treated with PTFE in multiple stages are seen to possess distinctly improved mechanical and electrochemical durability compared to GDLs treated with PTFE in a single stage. The difference in structure and hydrophobicity of the GDLs, when they are subjected to the two different PTFE treatment routes, are examined to understand the reasons for the improvements. The results indicate that there is a change in surface morphology, pore size distribution, and hydrophobicity of the GDL samples depending on the treatment route adopted. It is observed that it is possible to establish a gradient in PTFE profile in the GDL by adopting multistage treatment. Such gradients counteract loss in hydrophobicity resulting from compression cycles during cell assembly and carbon corrosion due to electrochemical aging. The results reveal that GDLs subject to multistage PTFE treatment, can have increased lifetime as opposed to conventional single stage PTFE treated GDL. ► PTFE treatment of GDL was carried out in multiple stages. ► Multiple stages of PTFE loading establish a gradient in PTFE distribution across the cross section. ► Such gradient is found to be useful in counteracting loss in hydrophobicity due to compression cycles and electrochemical aging.